2017
DOI: 10.1111/ced.13008
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor (TLR)7 expression in mycosis fungoides and psoriasis: a case-control study

Abstract: SummaryBackground. Toll-like receptors (TLRs) have been implicated in various dermatological diseases. TLR agonists have the capacity to potently activate the innate immune cells of patients with advanced, refractory, cutaneous T-cell lymphoma (CTCL). Aim. To detect TLR7 gene expression in mycosis fungoides (MF) (a neoplastic skin condition) and to compare it with psoriasis (an inflammatory skin condition) in an attempt to clarify the pathogenic role played by TLR7 in both conditions. Methods. This case-contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Furthermore, immunohistochemical staining revealed that TLR4 expression was upregulated in samples from patients with guttate psoriasis compared with samples from individuals with plaque psoriasis or normal skin [29]. The level of TLR7 mRNA in lesional skin from patients with psoriasis was significantly higher than that in healthy controls [30]. Real-time polymerase chain reaction (PCR) revealed that the expression levels of TLR3, TLR5, TLR6, TLR7, TLR9, and TLR10 in lesional skin were higher than those in peripheral blood mononuclear cells (PBMCs) of the same patients with psoriasis [31].…”
Section: Tlr Signaling and Psoriasismentioning
confidence: 94%
“…Furthermore, immunohistochemical staining revealed that TLR4 expression was upregulated in samples from patients with guttate psoriasis compared with samples from individuals with plaque psoriasis or normal skin [29]. The level of TLR7 mRNA in lesional skin from patients with psoriasis was significantly higher than that in healthy controls [30]. Real-time polymerase chain reaction (PCR) revealed that the expression levels of TLR3, TLR5, TLR6, TLR7, TLR9, and TLR10 in lesional skin were higher than those in peripheral blood mononuclear cells (PBMCs) of the same patients with psoriasis [31].…”
Section: Tlr Signaling and Psoriasismentioning
confidence: 94%
“…61 Notably, TLR2 and TLR7 also manifested an upregulation in the skin of individuals with psoriasis. 62,63 These revelations suggest that TLRs, specifically TLR3, TLR2 and TLR7, expressed in KCs, contribute to regulating pruritic skin diseases.…”
Section: Toll-like Receptorsmentioning
confidence: 99%
“…Toll-like receptors (TLRs) are a class of pattern-recognition receptors comprising more than 10 surface receptors important for pathogen recognition. The signaling mediated through TLRs and subsequent induction of cytokine release are important in various skin pathologies including MF ( 115 , 116 ). Treatment with TLR9 stimulators such as cytosine-phosphate-guanine (CpG) and oligodeoxynucleotides induces Th1-inducing cytokines, which have been proven to be clinically significant in MF and SS subjects ( 115 , 117 , 118 ).…”
Section: Tumor Microenvironment Of T-cell Lymphoma and The Role Of Cy...mentioning
confidence: 99%